Implementation of the Kaffah Concept in Rahn tasjily Contracts at Sharia Pawnshops as an Effort to Develop the Sharia Economy - Dewi Nawang Wulan; Ahmad Munir; Rahmat Setiawan; Ririn Novia Hidayati (JURNAL AKTA, 2026)
This study examines the application of the Kaffah principle in the rahn tasjily contract used by Sharia Pawnshops as an accessory contract to encumber customer collateral through the Arrum BPKB product. The research focuses on the position of Rahn tasjily as collateral with a review based on the Fiduciary Guarantee Law and DSN-MUI Fatwa Number 68 of 2008, while also analyzing the application of the Kaffah principle in the practice of these contracts at Pegadaian Syariah. The research method employs a conceptual approach, drawing on legal views and doctrines related to the Kaffah principle in Islamic economics. In addition, the research employs a legislative approach through a review of regulations related to the Rahn tasjily contract, as well as a case approach by analyzing Islamic economic dispute rulings pertaining to this contract. The results of the study show that the Kaffah principle has not been fully applied to the rahn tasjily contract at Pegadaian Syariah. This is due to its half-hearted nature, specifically the existence of a burden through the Fiduciary Guarantee on the Rahn tasjily contract and the absence of executory power in the contract. This condition renders the contract's application ineffective, necessitating further regulations, such as a Sharia Guarantee Law, to provide legal certainty for the rahn tasjily contract at Pegadaian Syariah.